Membranous nephropathy followed by anti-glomerular basement disease: a case report and review of clinical presentation and treatment - Speer, Claudius; Gaida, Matthias; Waldherr, Rüdiger; Nußhag, Christian; Kälble, Florian; Zeier, Martin (SAGE open medical case reports, 2018)
Membranous nephropathy is a common cause of nephrotic syndrome in adults and can be primary or secondary through autoimmune disease, medication, infection, or malignancy. Rapidly progressive glomerulonephritis with crescent formation is rare in patients with membranous nephropathy. Thus, in cases with rapid decline in renal function, after excluding complications such as malignant hypertension, acute hypersensitivity interstitial nephritis, and bilateral renal vein thrombosis, the simultaneous occurrence of a superimposed glomerulonephritis should be considered. We report a 55-year-old man suffering from a biopsy-confirmed primary membranous nephropathy, who developed rapidly progressive glomerulonephritis with anti-glomerular basement membrane antibodies after being affected with membranous nephropathy for 8 years. The kidney biopsy revealed a concurrence of membranous nephropathy and anti-glomerular basement membrane disease. Clinical presentation and treatment of membranous nephropathy followed by anti-glomerular basement membrane disease are discussed based on our observation with promising follow-up.
Gesehen am 01.04.2020